Modeling high quality solar system - Phua, Derek Joon Kiat. (2011)
Recent decades had opened a new dimension in astronomy through the emergence of fuel efficient rockets. The initiation of the space exploration program that makes use of these rockets for space exploration had led to many significant breakthroughs in astronomy.